Pattern of Childhood Malignancy in a Tertiary Care Hospital - Akter, Masuma; Morshed Khosru, AKM Amirul; Badruddoza, Shah Mohammad; Kabir, Enamul; Arbab Sarker, Mohammad; Ismail, Maymuna (Medicine Today, 2023)
Introduction: Cancer is a leading cause of death for children and adolescent worldwide. The cure rates in low middle-income countries are dismal (20%) in comparison to high income countries (80%). This study attempts to provide spectrum of pediatric malignancies from a tertiary care hospital in Bangladesh. Aim: Aim of this study is to evaluate the pattern of Childhood malignancy in a tertiary care hospital like Dhaka Medical College Hospital(DMCH). Materials and Methods: It is a prospective observational study was done in DMCH, over a period of 1 year (March 2014 to February 2015). After fulfilling the inclusion criteria, total 200 children aged 0-15 years were enrolled in this study. For classification of pediatric malignancies the International Classification of Childhood Cancer (ICCC), was followed. Results: Patients were stratified in 4 groups according to the age; 0-3 years, 3-6 years, 6-9 years and 9-12 years. Most of the patients fell in 6–9-year group (29%), followed by 3–6-year group (25%). Majority of cases, 61% were male. The male to female ratio was 1.55:1. Among200 cases, Leukemia (49%) was the most common malignancy followed by lymphoma, CNS Tumor, Neuroblastoma, Retinoblastoma, Wilms tumor and Malignant bone tumors. Acute lymphoblastic leukemia (ALL) comprises majority (98/200) of leukemia. Conclusion: This study gauges the trend of pediatric malignancies in Bangladesh, which is important in the planning and evaluation of health strategies. In Bangladesh, where there is dearth of high-quality data as we lack a dedicated pediatric cancer registry, such epidemiological studies play a significant part for this small but distinguished group of patients. Medicine Today 2023 Vol.35(2): 95-98